2020
DOI: 10.1002/jia2.25634
|View full text |Cite
|
Sign up to set email alerts
|

Greater dapivirine release from the dapivirine vaginal ring is correlated with lower risk of HIV‐1 acquisition: a secondary analysis from a randomized, placebo‐controlled trial

Abstract: Introduction: A vaginal ring containing 25 mg of the antiretroviral dapivirine has demonstrated efficacy in reducing women's risk of sexually acquiring HIV-1; however, imperfect ring use likely diluted efficacy estimates in clinical trials. The amount of dapivirine remaining in returned rings may reflect the extent of product use, permitting estimation of HIV protection in the context of consistent use. Methods: We measured the amount of dapivirine in returned rings from a placebo-controlled trial of the dapiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…Women were randomized in a 1:1 ratio to use either a monthly silicone elastomer vaginal matrix ring containing 25 mg of dapivirine or a placebo ring containing no drug, and followed monthly for a minimum of 12 and a maximum of 33 months. Study results demonstrated a statistically signi cant reduction in HIV risk among participants assigned to the dapivirine ring by 27% in intention-to-treat analyses [3], and suggested greater risk reduction among subgroups with evidence of high adherence, exceeding 50% among individuals with consistent ring use [3,17]. Additional details regarding the study design, recruitment, and results have been published previously [3].…”
Section: Methodsmentioning
confidence: 88%
“…Women were randomized in a 1:1 ratio to use either a monthly silicone elastomer vaginal matrix ring containing 25 mg of dapivirine or a placebo ring containing no drug, and followed monthly for a minimum of 12 and a maximum of 33 months. Study results demonstrated a statistically signi cant reduction in HIV risk among participants assigned to the dapivirine ring by 27% in intention-to-treat analyses [3], and suggested greater risk reduction among subgroups with evidence of high adherence, exceeding 50% among individuals with consistent ring use [3,17]. Additional details regarding the study design, recruitment, and results have been published previously [3].…”
Section: Methodsmentioning
confidence: 88%
“…Two randomized, placebo controlled, phase III trials in healthy sexually-active women, MTN-020/ASPIRE and IPM-027/The Ring Study, demonstrated the monthly DVR was well-tolerated and reduced HIV incidence [ 4 , 5 ]. In ASPIRE, higher risk reduction was estimated with measures indicating higher adherence [ 6 ]. In earlier phase I and II trials the DVR was found to be highly acceptable [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of these oral and vaginal PrEP strategies are driven by user adherence (12,13), which can be challenging (14)(15)(16), especially with daily dosage. As such, innovative strategies to support adherence are warranted, including in pregnant and breastfeeding women, an important population for PrEP.…”
Section: Introductionmentioning
confidence: 99%